2013
DOI: 10.1007/s00383-012-3255-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined free autologous auricular cartilage and fascia lata graft repair for a recurrent tracheoesophageal fistula

Abstract: Repair of recurrent tracheoesophageal fistula (TEF) after repair of congenital esophageal atresia continues to be a difficult problem. The most common re-operation for a recurrent TEF involves repair via a right thoracotomy and use of a flap as interposed tissue between the closure sites. Although several materials have been reported for recurrent fistula repair, natural pedicled flaps have been used in most previous reports. The harvesting of a pedicled flap can sometimes be difficult when the patient has had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The placement of viable tissue between the suture lines may help to prevent the further recurrence of TEF [5, 6, 9, 10]. Previous studies have described the use of the pericardium, pleura, intercostal flap, cervical muscle flap, cartilage, and lymph nodes for this purpose [5, 6, 9, 10]. The flap can be harvested from the same surgical site with its own blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The placement of viable tissue between the suture lines may help to prevent the further recurrence of TEF [5, 6, 9, 10]. Previous studies have described the use of the pericardium, pleura, intercostal flap, cervical muscle flap, cartilage, and lymph nodes for this purpose [5, 6, 9, 10]. The flap can be harvested from the same surgical site with its own blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported the effects of the interposition of viable tissue, as a flap, between the suture lines of the trachea and esophagus to prevent further recurrence in patients with recurrent TEF [9, 10]. We experienced a rare case in which a TEF recurred in the cervical area on the 10th year after the primary repair.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, costal cartilage graft could also be used especially in cases that were experienced tracheal injury in the initial surgery (25). The other rarely used are omental flap (26) and combination of free auricular and fascia lata graft (27). There is no literature data supporting one tissue in preventing fistula recurrence.…”
Section: Management Of Rectefmentioning
confidence: 99%
“…Free autologous auricular and costal cartilage grafts have been used to close large tracheal defects that have resulted from division of rTEFs. 41,42 If adequate repair of the fistula and esophagus is not possible secondary to inflammation and inadequate tissue, esophageal replacement may be necessary.…”
Section: Open Surgical Therapiesmentioning
confidence: 99%